Fumigant toxicity from five essential oils rich in ketones against Sitophilus zeamais (Motschulsky) - Herrera, J. M. (2014)
Essential oils (EOs) and individual compounds act as fumigants against insects found in stored products. In fumigant assays, Sitophilus zeamais Motschulsky adults were treated with essential oils derived from Aphyllocladus decussatus Hieron, Aloysia polystachya Griseb, Minthostachys verticillata Griseb Epling and Tagetes minuta L , which are rich in ketones and their major components: α- thujone, R-carvone, S-carvone, (-) menthone, R (+) pulegone and E-Z- ocimenone. M. verticillata oil was the most toxic ( LC50: 116.6 µl /L air) characterized by a high percentage of menthone (40.1%) and pulegone (43.7%). All ketones showed insecticidal activity against S. zeamais. However, pulegone (LC50: 11.8 µl/L air), R- carvone (LC50: 17.5 µl/L air), S-carvone (LC50: 28.1 µl/L air) and E-Z-ocimenone (LC50: 42.3 µl/L air) were the most toxic. These ketones are a,b-unsaturated carbonyl. This feature could play a fundamental role in the increase of insecticidal activity against S. zeamais.